Efficacy of exercise training in symptomatic patients with hypertrophic cardiomyopathy: Results of a structured exercise training program in a cardiac rehabilitation center. (January 2015) - Klempfner, Robert; Kamerman, Tamir; Schwammenthal, Ehud; Nahshon, Amira; Hay, Ilan; Goldenberg, Ilan; Dov, Freimark; Arad, Michael
Background: Recent data suggest that exercise training (ET) confers significant symptomatic and functional improvements in patients with diastolic dysfunction, and thus may be beneficial in patients with hypertrophic cardiomyopathy (HCM). However, there are no data regarding the safety or efficacy of ET in HCM patients. Design: A prospective non-randomized intervention design was used. Methods: We enrolled 20 patients with symptomatic HCM, significantly limited in everyday activity, into a supervised cardiac rehabilitation exercise program. Results: Patients were 62 ± 13 years old, in New York Heart Association (NYHA) functional class II (35%) or III (65%), had a mean interventricular septum dimension of 17 ± 5 mm and left ventricular ejection fraction (LVEF) of 53 ± 15%. Left ventricular outflow gradient was present at rest in nine patients (mean 51 ± 24 mm Hg) and six patients had an implantable defibrillator. Exercise prescription was based on heart rate reserve (HRR) determined from a symptom-limited graded exercise stress test. Exercise intensity was gradually increased from 50% to 85% of the HRR over the training period. Patients completed an average of 41 ± 8 hours of aerobic ET. No adverse events or sustained ventricular arrhythmias occurred during the training program. Functional capacity, assessed by a graded exercise test, improved from 4.7 ± 2.2 to 7.2 ± 2.8 metabolic equivalents (METs) ( p = 0.01). NYHA functional class improved from baseline by ≥1 grade in 10 patients (50%) and none experiencing deterioration during follow-up. Conclusions: The present study suggests that patients with HCM who remain symptomatic despite medical therapy may achieve considerable functional improvement through a supervised ET program.